Moral Economic Behavior of Small-Medium Enterprises in Three Provinces During the Covid-19 Pandemic - Nasrullah Widiantoro Sandi (Universitas Airlangga, 2021)
The purpose of this research is to identify the condition of MSMEs and the actions taken to survive the COVID-19 pandemic. The subjects in this study were MSMEs in three provinces, namely East Java (Surabaya and Gresik), Central Java (Pekalongan and Cilacap), and Riau (Pekanbaru). The method used in this research is a literature review with a descriptive research type. This means that the data in this study are secondary data from the research results of other researchers. The literature sources in this thesis are five journals of research results on MSMEs in East Java (Surabaya and Gresik), Central Java (Pekalongan and Cilacap), and Riau (Pekanbaru) during the COVID-19 pandemic. To carry out the analysis, the researcher used the concept of J. Scott's (1981) moral economic behavior theory which has two basic assumptions. It is a subsistence economy and safety-first behavior to avoid risk. The results, first, the researchers looked at the conditions of MSMEs in East Java, Central Java, and Riau which was in a subsistence condition or was in minimal conditions during the COVID-19 pandemic such as decreased sales turnover, difficulty in raw materials, reduced consumers due to social restrictions and regulations. the distribution system was also obstructed because of the social restrictions imposed by the government. Second, the researchers also looked at the moral economic behavior & safety first of MSME actors in two categories. The first category is the one that has a positive impact on the behavior such as improving the quality of production, keeping product prices affordable, and maintaining good relations with consumers to form consumer loyalty to MSMEs. Then, for the second category, those that have a negative impact on the sustainability of MSMEs in the midst of a pandemic can be seen in the use of conventional marketing methods, lack of innovation in products and some even implement a “loss-sold” as long as it can be sold; strategy because of lack of product quality and to minimize losses.